Penguatan Nilai-Nilai Pancasila sebagai Solusi Preventif untuk Mencegah Kenakalan dan Kriminalisasi Anak di Masyarakat - Nisa', Ihda Shofiyatun; Muslimin, Muslimin; Putra, Muhammad Evendi; Lazwar, Sulaiman (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Delinquency and criminalization of children is a social problem caused by various factors, including environmental influences, lack of understanding of moral values, and weak supervision from the family and community. This service program aims to strengthen Pancasila values ​​as a preventive solution in shaping children's character so that they comply with social and legal norms. The method used in this activity is educational participatory, involving the school academic community, including teachers, teaching staff, and students as the main objects. Activities are carried out through outreach, interactive discussions, case studies, teacher training, and student involvement in various social programs based on Pancasila values. Evaluation is carried out to measure the effectiveness of the program through surveys, interviews and observations of changes in student behavior before and after the program is implemented. The results of the service showed that 85% of students experienced an increase in understanding and application of Pancasila values, and there was a 40% reduction in deviant behavior, such as bullying.